Democratic consolidation in Eastern Europe. Vol. 1, Institutional engineering - Zielonka, Jan, 1955- (Oxford : Oxford University Press, 2001)
This collection of papers is part of a series on democratic consolidation in post-communist Central and Eastern Europe. This first volume analyses constraints on and the opportunities provided by institutional engineering.
13. Slovakia: From the Ambiguous Constitution to the Dominance of Informal Rules -- 14. Slovenia: From Elite Consensus to Democratic Consolidation -- 15. Hungary's Pliable Constitution -- 16. Legitimacy: The Price of a Delayed Constitution in Poland -- 17. Conclusions: On the Relevance of Institutions and the Centrality of Constitutions in Post-communist Transitions -- Selected Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- Y -- Z.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Democratization -- Europe, Eastern; Democratization -- Former Soviet republics; Constitutional history -- Europe, Eastern; Constitutional history -- Former Soviet republics; Europe, Eastern -- Politics and government -- 1989-; Former Soviet republics -- Politics and government; Démocratisation -- Europe de l'Est.; Démocratisation -- Ex-URSS.; Histoire constitutionnelle -- Europe de l'Est.; Histoire constitutionnelle -- Ex-URSS.; Europe de l'Est -- Politique et gouvernement -- 1989-; POLITICAL SCIENCE -- Political Process -- General; Constitutional history; Democratization; Politics and government; Eastern Europe; Soviet Union -- Former Soviet republics; Since 1989